THE INFLUENCE OF SELF EFFICACY, KNOWLEDGE SHARING, AND HUMAN RELATIONS ON EMPLOYEE PERFORMANCE AT PT ABDAEL NUSA IN SURABAYA - Kadek Dedy Adnyana; Sri Rahayu; Sundjoto; Rifda Fitrianty (RADJA PUBLIKA, 2025)
This study aims to analyze the effect of Self Efficacy, Knowledge Sharing, and Human Relations on employee performance at PT. Abdael Nusa in Surabaya, both partially and simultaneously. The type of research employed is quantitative research with an associative approach. The population of this study consists of all employees of PT. Abdael Nusa in Surabaya totaling 67 employees, and the entire population was used as the research sample through the census sampling technique. Data collection techniques included questionnaire distribution, documentation, and literature review. The data analysis techniques used comprised data quality testing, classical assumption testing, multiple linear regression analysis, partial testing, simultaneous testing, and coefficient of determination analysis. The results of the study indicate that Self Efficacy partially has a significant effect on employee performance, while Knowledge Sharing and Human Relations partially do not have a significant effect on employee performance. However, simultaneously, Self Efficacy, Knowledge Sharing, and Human Relations have a significant effect on employee performance at PT. Abdael Nusa in Surabaya.